2004
DOI: 10.1128/mcb.24.5.2012-2024.2004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Drosophila Wingless Signaling Pathway Based on RNA Interference

Abstract: Regulation of Armadillo (Arm) protein levels through ubiquitin-mediated degradation plays a central role in the Wingless (Wg) signaling. Although zeste-white3 (Zw3)-mediated Arm phosphorylation has been implicated in its degradation, we have recently shown that casein kinase I␣ (CKI␣) also phosphorylates Arm and induces its degradation. However, it remains unclear how CKI␣ and Zw3, as well as other components of the Arm degradation complex, regulate Arm phosphorylation in response to Wg. In particular, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 50 publications
0
47
0
1
Order By: Relevance
“…stabilizing b-catenin, Bajpai et al, 2004). In agreement with this positive effect, inhibition of the C subunit of PP2A using RNAi in a Drosophila cultured cell line demonstrated that the absence of PP2A results in slightly decreased levels of Armadillo (the Drosophila b-catenin) in the absence of Wnt signaling (Matsubayashi et al, 2004). However, inhibition of PP2A did not appear to have a significant effect on the Wnt induced inhibition of Armadillo, indicating that PP2A may not be essential in the destruction complex, at least in this Drosophila cell line.…”
Section: Protein Phosphatase 2amentioning
confidence: 52%
See 2 more Smart Citations
“…stabilizing b-catenin, Bajpai et al, 2004). In agreement with this positive effect, inhibition of the C subunit of PP2A using RNAi in a Drosophila cultured cell line demonstrated that the absence of PP2A results in slightly decreased levels of Armadillo (the Drosophila b-catenin) in the absence of Wnt signaling (Matsubayashi et al, 2004). However, inhibition of PP2A did not appear to have a significant effect on the Wnt induced inhibition of Armadillo, indicating that PP2A may not be essential in the destruction complex, at least in this Drosophila cell line.…”
Section: Protein Phosphatase 2amentioning
confidence: 52%
“…A possible complication to the latter study is that prolonged Wnt stimulation reduces Axin levels (Willert et al, 1999), and CK1a phosphorylation of b-catenin depends on Axin in vertebrate cells (Amit et al, 2002;Liu et al, 2002). A subsequent study using both vertebrate and invertebrate cells demonstrated no effect of Wnt signaling on the CK1a phosphorylation of b-catenin (Matsubayashi et al, 2004). Instead, these authors demonstrated a clear inhibition of GSK3 phosphorylated b-catenin in mouse L cells in response to Wnt, and mixed results in their insect cell lines.…”
Section: B-cateninmentioning
confidence: 95%
See 1 more Smart Citation
“…The cytoplasmic isoforms a, d, and 1 can bind to Axin, and purified CK1a, d, or 1 can phosphorylate b-catenin at S45 (Amit et al 2002). RNAi experiments in both mammalian cells and Drosophila and genetic experiments in mice indicate that CK1a is the principal isoform responsible for phosphorylating Ser45 (Liu et al 2002;Matsubayashi et al 2004;Elyada et al 2011).…”
Section: Phosphorylation By the Destruction Complexmentioning
confidence: 99%
“…The ability of these kinases to phosphorylate Arm in the absence and presence of GST-Hipk was evaluated by using an anti-phospho-β-catenin (S33/S37) antibody. As the consensus phosphorylation sites (along with the region surrounding them) at the N terminus of β-catenin are perfectly conserved in Arm (8), the antibody that recognizes β-catenin phosphorylated at serine 33 and serine 37 also recognizes the corresponding phospho-epitope in Arm, serine 44 and serine 48 (20). We find that GST-Hipk did not inhibit the ability of CK1 and Sgg to phosphorylate Arm in vitro ( Fig.…”
Section: Resultsmentioning
confidence: 69%